Skill acquisition and Korean landscape architecture: An ethnographic account of skateboarding in Seoul, South Korea - Holsgens, S. (Journal of Sport and Social Issues, 2019)
This article sketches a phenomenology of South Korean skateboarding. Drawing on more than 6 years of experience in the region and 20 months of fieldwork, I explore how Seoul-based skaters negotiate their presence in the built environment through precise spatial expertise, minute bodily gestures, and everyday skillful learning. Specifically, I think through the ways in which architectural minutiae within skate parks affect the skaters` perceptual experience of the built environment. Significantly, the architectural typology of the Korean skate parks is experienced as spaces of stillness, closeness, and tranquility, providing a serene and placid alternative to the interpretation of skateboarding as a fundamentally spectacular and trick-driven practice.